2001
DOI: 10.1046/j.1463-1326.2001.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of incretin‐like salivatin in saliva from patients with type 2 diabetes and in parotid glands of streptozotocin‐diabetic BALB/c mice

Abstract: The above results suggest that salivatin lowers hyperglycaemia after meal and sustains the normal blood glucose levels by incretin-like mechanisms. The function may be damaged by diabetes, and this in turn might make the diabetes worse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The finding of less reactive statherin in secretory granules suggests a diminished secretion of this protein. Many data documented that diabetes causes altered concentration of salivary proteins, some appearing reduced such as proline‐rich proteins, EGF and salivatin, other increased such as those related with inflammatory response (Aydin, 2007; Dodds et al , 2000; Kasayama et al , 1989; Kimura et al , 2001; Szczepanski et al , 1998). In the same way, secretory protein levels appeared changed in many human exocrine epithelia such as exocrine pancreas and lacrimal gland (Stolwijk et al , 1994; Williams and Goldfine, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The finding of less reactive statherin in secretory granules suggests a diminished secretion of this protein. Many data documented that diabetes causes altered concentration of salivary proteins, some appearing reduced such as proline‐rich proteins, EGF and salivatin, other increased such as those related with inflammatory response (Aydin, 2007; Dodds et al , 2000; Kasayama et al , 1989; Kimura et al , 2001; Szczepanski et al , 1998). In the same way, secretory protein levels appeared changed in many human exocrine epithelia such as exocrine pancreas and lacrimal gland (Stolwijk et al , 1994; Williams and Goldfine, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…As judged from the literature, salivary gland proteins as well as their concentrations in the saliva do not show a uniform pattern in response to diabetes, for instance increased levels of amylase and IgA (Piras et al , 2010; Aydin, 2007) but reduced ghrelin, salivatin, epidermal growth factor and proline‐rich proteins (Kasayama et al , 1989; Szczepanski et al , 1998; Kimura et al , 2001; Aydin, 2007). The cause of changed protein expression in diabetes is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…An increased susceptibility to bacterial infections, inflammation, caries, xerostomia, and periodontal disease often associated with diabetes (Lin et al , 1999; Hirsch, 2004; Javed et al , 2007; Patiño Marín et al , 2008; Siudikiene et al , 2008) was related with a malfunctioning of salivary glands resulting in insufficient salivary flow and altered protein secretion (Kasayama et al , 1989; Kimura et al , 2001; Aydin, 2007). In agreement with this statement, we recently found a strongly reduced statherin reactivity in submandibular glands of patients with diabetes with respect to normal ones (Isola et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the role of PRPs in oral calcium disposition, relatively little is known about Peptide P-C from a biological perspective. Recent studies demonstrated that it can modulate blood glucose levels after feeding by inducing insulin release and lowering glucagon levels [15,16]. Additional studies are needed to elucidate the biological significance of each Peptide P-C variant.…”
Section: Discussionmentioning
confidence: 99%
“…Acidic PRPs are thought to be involved in calcium homeostasis in the oral cavity and act by preventing calcium phosphate precipitation that is necessary for maintaining tooth enamel integrity. Also, recent studies have demonstrated that Peptide P-C can modulate blood glucose levels after feeding by inducing insulin release and by restricting glucagon release [15,16]. The Peptide P-C variants have a nominal mass in the 4370 -4372 Da range with overlapping isotopomer distributions that were resolved only with a Fourier-transform ion cyclotron resonance (FTICR) mass spectrometer operating at 750,000 resolving power.…”
mentioning
confidence: 99%